EFEKTIVITAS LATIHAN IMAGERY SHOOTING PUNGGUNG KAKI DAN IMAGERY SHOOTING UJUNG KAKI TERHADAP AKURASI TENDANGAN FUTSAL - Pundani Azzahusna; Sungkowo Sungkowo (Unnes Journal of Sport Sciences, 2023)
The purpose of this study was to determine the effect of imagery training on the results of goal kicks. This study uses experimental research methods. The instrument used is the Shooting Accuracy test. The validity of the test using content validity included face and logical validity with the reviewers seeing that the test was good in terms of the appearance of the test. The reliability coefficient of shooting with the instep was 0.940 and shooting with the toe was 0.967. The research sample was the female futsal athlete U-19 Five Star Club. The data analysis technique uses the T-test. The results of the t-test: sig. (2-tailed) pretest and posttest instep shooting of 0.001 <0.05 with a t count of 7.032 > t table of 2.447. sig. value (2-tailed) pretest and posttest shooting toe of 0.000 <0.05 with a t count of 17.393> t table of 2.447 so that it means there is an influence between imagery training on increasing the results of shooting accuracy for female futsal athletes U-19 Five Star Club. sig. value (2-tailed) instep shooting posttest and toe posttest 0.000 <0.05 with a t count of 7.840> t table 2.447 which means that the use of imagery training methods for instep shooting has a better level of effectiveness than the shooting.